2019
DOI: 10.3897/folmed.61.e47958
|View full text |Cite
|
Sign up to set email alerts
|

Can 3D Vision Improve Laparoscopic Performance in Box Simulation Training when Compared to Conventional 2D Vision?

Abstract: Introduction: Three-dimensional (3D) imaging systems have been introduced in laparoscopic surgery to facilitate binocular vision and dexterity to improve surgical performance and safety. Several studies have shown the benefits of 3D imaging in laparoscopy, but until now only a few studies have assessed the outcome by using objective variables. Box trainers are affordable alternatives to virtual laparoscopic surgical training, and the possibility of using real surgical instruments makes them more realistic to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The 2D video box trainer is similar to the setup used in standard laparoscopic surgery, and hence the difference in results between 2D and 3D simulators are interesting. Other studies comparing 3D simulators to 2D simulators have shown shortening of learning curves and improved results for box trainers and VR simulator with 3D [ [34] , [35] , [36] ]. No major difference has been shown between performance in 2D box trainers and 2D VR trainers amongst residents, apart from a small possible benefit of using real instruments in the box trainer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2D video box trainer is similar to the setup used in standard laparoscopic surgery, and hence the difference in results between 2D and 3D simulators are interesting. Other studies comparing 3D simulators to 2D simulators have shown shortening of learning curves and improved results for box trainers and VR simulator with 3D [ [34] , [35] , [36] ]. No major difference has been shown between performance in 2D box trainers and 2D VR trainers amongst residents, apart from a small possible benefit of using real instruments in the box trainer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that researchers tended to integrate two or more techniques into a single system to establish a more effective method. The combination of different advanced methods could offset the weaknesses of a single technique, such as laparoscopic training integrated with 3D printing 21 , or VR 27 , 28 . After rigorous simulator training, trainees can better perform laparoscopic procedures in the operation room 29 .…”
Section: Discussionmentioning
confidence: 99%